PERANCANGAN WATER HEATER KAPASITAS 0,1 LITER PER DETIK DENGAN MEMANFAATKAN PANAS MATAHARI UNTUK MENDUKUNG KETAHANAN ENERGI - Hamdani, Taufik; Sudarmanto, Sudarmanto; Setiabudi, Dedet Hermawan; Mardwianta, Benedictus; ahmadi, Nurfi; subarjo, Abdul haris; irawati, Mardiana (Institut Teknologi Dirgantara Adisutjipto, 2023)
Population growth and technology development are increasing rapidly. These cause the use of energy on the earth is increasing. One effort to obtain energy sources is to utilize solar energy using solar water heater. This research was expected to help the society to save energy derived from fossils. A testing was conducted by designing solar water heater with collector size of 60 cm x 50 cm using black painted aluminum-coated styrofoam insulator and the storage tank made of stainless steel with volume of 40 liter using black painted aluminum-coated styrofoam. In conducting the testing, the data were taken at 09.00 a.m until 04.00 p.m for 5 days. The research was conducted at ITD Adisutjipto. The analysis and discussion showed the solar water heater design and the storage tank used to perform performance the test (efficiency). Within 5 days testing the average of water temperature out (Tout) was 59.75 oC to 76.59 oC with the average rate efficiency of 54.07 % to 54.9 % and the average storage drop rate of 2.97 K / Hr or 17.84 K for 6 hours